2006
DOI: 10.1177/08830738060210110701
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin for Guillain-Barré Syndrome: How Effective?

Abstract: Guillain-Barré syndrome is an acute inflammatory demyelinating neuropathy characterized by progressive symmetric polyradiculoneuritis, predominantly manifested by weakness and areflexia. In this article, we report our findings in 25 children treated with intravenous immunoglobulin and compare them with the remaining 30 children who received supportive care only. Only supportive care was given to 30 children who were not able to receive intravenous gammaglobulin because of shortcomings in intravenous gammaglobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
0
12
0
4
Order By: Relevance
“…In summary, the evidence shows that IVIG reduced time to return of function in one RCT, one cohort study, and one series ( n =150), but not in one cohort study with increased disease severity in the IVIG arm ( n =55) . Treatment with 2g/kg of IVIG divided over 2 days did not affect overall outcome, but was associated with secondary transient deterioration compared with treatment over 5 days (5 out of 23 vs 0 out of 23; p =0.049) .…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In summary, the evidence shows that IVIG reduced time to return of function in one RCT, one cohort study, and one series ( n =150), but not in one cohort study with increased disease severity in the IVIG arm ( n =55) . Treatment with 2g/kg of IVIG divided over 2 days did not affect overall outcome, but was associated with secondary transient deterioration compared with treatment over 5 days (5 out of 23 vs 0 out of 23; p =0.049) .…”
Section: Resultsmentioning
confidence: 90%
“…IVIG was associated with a longer duration of mechanical ventilation . A cohort study ( n =55) comparing IVIG with supportive care found no difference in maximal disability grade or time to improvement . Treatment was allocated according to IVIG availability, and the treatment group had higher rates of ventilation, mortality, and severe disability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One multicenter randomized study from Western Europe found that early treatment with IVIG was associated with earlier motor recovery [31]. Other studies show that IVIG was no better than supportive care, although the time from symptom onset to maximum symptom severity was shorter in patients who received IVIG within 10 days than patients who did not receive IVIG [32]. Both efficacy and non-efficacy have been documented in children with GBS, and most of these studies are limited by small study design.…”
Section: The Therapeutic Role Of Ivigmentioning
confidence: 97%
“…Тем не менее, в детской популяции по миру не отмечена разница в полноте восстановления между формами СГБ спустя год после начала заболевания. Дети, перенесшие как ОВДП, так и ОМАН/ ОМСАН, имеют очень хороший прогноз в плане восстановления двигательных функций [10,11]. Имеются ли различия в протекании аксональных и демиелинизирующих форм у детей в нашей стране, в настоящее время не известно.…”
unclassified